ANALISIS KEKERABATAN POPULASI ULAR Malayopython reticulatus (Schneider, 1801) DI KEPULAUAN SULAWESI SELATAN BERDASARKAN KARAKTER MORFOLOGIS DAN MOLEKULAR - , Berry Fakhry Hanifa; , Dr. Budi Setiadi Daryono, M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Malayopython reticulatus is widely spread from South Asia to Southeast Asia, including most of Indonesian islands except Papua and surrounding apart. Malayopython reticulatus divided into three subspecies based on morphological characters and molecular data. Geographical barrier does exist among populations which result the formation of a new subspecies. The latest two subspecies described from population of Selayar Island and Tanahjampea (South Sulawesi). However, there are some populations have distinctive morphological characters and not recorded yet such Karumpa, Honey/Madu, and Kalaotoa Islands (South Sulawesi). This study purpose was to identify morphological and molecular characters of Malayopython reticulatus population of related islands and examine the phylogenetic relationship among them. This study was divided into two steps, first is to identify morphological character including morphometric, head scale character, and body scales. Later step is DNA isolation and sequencing of cytochrome b. BLAST software, DNA Baser, ClustalX and Mega5 will be used to analyze the data and construct phylogenetic trees by using maximum likelihood, maximum parsimony, and neighbor joining method. The result showed that these samples has a very close relationship each other as close as to M. r. reticulatus and M. r. jampeanus rather than to M. r. saputrai. It was highly suspected that these samples was a missing links which can be used as âstepping stoneâ of M. reticulatus dispersal from Lesser Sunda to Jampea Island.